Optimization of prismatic moon pool configuration by operability criteria - MICHIMA, Paula Suemy Arruda (2017)
A moon pool is an opening inside the hull of a floating system that allows access to the sea isolated from horizontal environmental forces. Despite those benefits, some disadvantages may occur when a resonant response to waves happens. Exaggerated oscillations might cause poor operation conditions or interruption of drilling procedures. The aim of this work is to, given a hull, find an optimal moon pool configuration that would result in the best stationary operation conditions for a typical sea state of the operation region. The proposal restricts it to be prismatic, free of appendages, recess, or any solution other than adequate contour shape. A drill ship is chosen as an example, but the method suits for floating systems in short and long term operation, granted that the response spectra can be calculated. Through an altered genetic algorithm applied to the set of parameters that define the shape and dimensions of the moon pool border, the optimum shape is searched based on hull and internal water response to wave excitation in various incidence angles and significant wave periods. A detailed development of the potential model used to describe the ship and free surface motions is presented, proposing a Rayleigh damping term and a boundary condition at the free surface inside the moon pool. The derivation of a set of formulae to transform into threshold significant wave height the acceptable limit values of each criterion: free surface height, ship motion, hull structure strength and positioning in azimuthal plane are also shown to determine a grade of fitness based on resultant operable conditions. Although there still are spaces for improvement of the resultant parameters’ values due to computational limitations, transversal dimensions and border shape parameters have converged, and the small variation of longitudinal dimensions is limited by order of length and Length/Breadth ratio values range of the moon pool. It was found possible to define, from user input: hull geometry and limit values for operability, what is the optimum prismatic moon pool configuration, which can be very different from the standard rectangle. Further, once the results of optimization are obtained, still in design stage, it is possible to identify characteristics of the system (or ship) that would improve operability. The output of the optimization program provides a visualization file of the mesh of the hull with optimum moon pool, and a radar chart with the operable zone of a given sea state. The latter can be used for quick decision making upon interruption of procedures during operation. In terms of construction complexity the moon pool shape doesn’t seem to present any limitations, since it is prismatic. A bow or stern shape is much more complex than the moon pool, and from mesh definition it is composed of only flat plates, demanding no extra work in plate conformation.